Reduce the Risk of Failure of The Automotive Part Manufacturing Process using PFMEA AIAG-VDA: Case Study of Automotive Motorcycle Supplier in Indonesia - Suryadi Ali; Choesnul Jaqin (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
Competition in the automotive industry, especially in Indonesia, is quite tight. Automotive OEMs require their suppliers, both Tier-1 and Tier-2, to supply quality products consistently. One of the indicators of supplier evaluation is the quality performance with abnormal product quality detection parameters from supplier to automotive OEM, and even to end-user if this happens on motorcycles. For this reason, this research aims to analyze and improve supplier performance level, mainly the manufacture of OEM motorcycle spare parts, by looking at the risk of production process failure. The method analyses for this research use AIAG-VDA PFMEA to analyze this starting from the closest case or the occurrence of abnormal violations on the assembly of OEMs and even end-users of motorcycles. The results showed that one of the suppliers processing with the lowest value, the Cap Camshaft product, in the casting process, there was a crack failure on the product. The cause of cracking by analyzing the casting process found that was due to bile on the casting and the instability of the bolting assembly area caused cracking on the camshaft cover. The repaired item standardizes the Nozzle Spray Die on Dies' lubrication direction and increases the level of abnormal detection, especially cracks with color detector inspection items. The Purpose of improvement proposals is to analyze the process with risk forecasting patterns and avoid process failures and even flow to customers.